Implementasi Asesmen Diagnostik Dalam Meningkatkan Hasil Belajar Siswa SMP Negeri 1 Cikalongwetan - Eka Wahyuningsih; Ineu Maryani (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
This research was based on the phenomenon of not yet optimal implementation of diagnostic assessments in social studies learning, especially in the Topography of the Asian Continent material in Class IX students who are still using the Curriculum 2013 at SMPN 1 Cikalongwetan. The research method uses a qualitative approach with data collection methods including interviews, observation, and documentation, with the main informants including social studies teachers and student representatives from classes IX-E, IX-F, and IX-G. The results found that teachers prepared teaching tools, models and methods according to their respective interest groups, prospects and learning styles. Student responses were quite varied, indicating readiness and capacity to receive the material and students' ability to understand the material. Most students have demonstrated good communication skills which are supported by the teacher's ability to communicate with students.